THE PHRASEOLOGY OF IVAN MAZEPA’S BUSINESS DOCUMENTATION IN THE CONTEXT OF THE UKRAINIAN LANGUAGE PHRASEOLOGICAL FUND DEVELOPMENT - Vasyl V. Denysiuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2022)
The aim of the article is a structural-semantic analysis of the idiom рукою власною (by one’s own hand) in Ivan Mazepa’s documents in the general context of the Ukrainian language phraseological fund development. The texts of the Hetman Chancellery during the Imperial-Soviet era had an unspoken status of non grata in linguistics, therefore there was a kind of taboo on involving them in the orbit of linguistic studies. To achieve the aim, it was necessary to complete the following tasks: to identify the declared idiom in Ivan Mazepa’s business discourse; to determine the semantics of the idiom; to reveal semantic and structural innovations of the idiom in time and space, caused by individual reception of the situation and the phraseological potential of linguistic units, which will make it possible to trace the Ukrainian language phraseological fund durability. To achieve the aim, the following methods were used: the descriptive method made it possible to analyze the specifics of the semantics of phraseological units; the method of contextual analysis was decisive for clarifying the peculiarities of phraseological units functioning in monuments of various styles and genres, which made it possible to determine shifts in the semantic structure of word combinations; with the help of the structural method, the connections between components of the idiom are traced; the comparative-historical method makes it possible to present the vertical development and dynamics of the set expression; the etymological method was used to confirm the specific or borrowed character of the phraseology. The set expression is a linguistic calque of the Latin manu propria and got into the Ukrainian language through Polish language. However, the functioning of the idiom своею рукою (by one’s own hand) «personally» in the Ukrainian language of the 15th century gives us a reason to talk about semantic, structural and stylistic syncretization in the Polish-Ukrainian era with the adapted in Polish variant ręką własną. The idiom demonstrates the complete dominance of the variant with the attribute власний (own) and a fairly stable trend to use exactly the indirect word order which corresponds to the «noun + adjective» model. However, the laws of Ukrainian syntagmatics led to the entry and functioning of set expressions in the new Ukrainian language with a direct order of components, attesting data from the Ukrainian language corpora. The inflection of the instrumental case, which is sporadically recorded in a reduced form, also demonstrates its historical persistence. Conclusion. The conducted research proved that the use of the idiom рукою власною (by one’s own hand) in Ivan Mazepa’s business documentation was a complete reflection of its use and changes in the contemporary Ukrainian language. Its use primarily in the texts of business communication, and later also in the texts of other styles and genres, proves the development and persistence of the lack of general semantics «personally» expressiveness over the centuries. Semantic identity made it possible to vary the attributive component, and the identity of business situations led to the complete ellipticity of this word combination in the direction of one word, which is characteristic, however, only of business sphere texts, which in the 18th century testify to the transfer of the practice of abbreviations developed in Western European offices for business set expressions.